Coculture of endothelial progenitor cells and mesenchymal stem cells enhanced their proliferation and angiogenesis through PDGF and Notch signaling. Issue 11 (16th October 2017) - Liang, Tangzhao; Zhu, Lei; Gao, Wenling; Gong, Ming; Ren, Jianhua; Yao, Hui; Wang, Kun; Shi, Dehai
Abstract : The beneficial effects of combined use of mesenchymal stem cells (MSCs) and endothelial progenitor cells (EPCs) on tissue repair and regeneration after injury have been demonstrated, but the underlying mechanism remains incompletely understood. This study aimed to investigate the effects of direct contact coculture of human bone marrow‐derived EPCs (hEPCs)/human bone marrow‐derived MSCs (hMSCs) on their proliferation and angiogenic capacities and the underlying mechanism. hEPCs and hMSCs were cocultured in a 2D mixed monolayer or a 3D transwell membrane cell‐to‐cell coculture system. Cell proliferation was determined by Cell Counting Kit‐8. Angiogenic capacity was evaluated by in vitro angiogenesis assay. Platelet‐derived growth factor‐BB (PDGF‐BB), PDGF receptor neutralizing antibody (AB‐PDGFR), and DAPT (a γ‐secretase inhibitor) were used to investigate PDGF and Notch signaling. Cell proliferation was significantly enhanced by hEPCs/hMSCs 3D‐coculture and PDGF‐BB treatment, but inhibited by AB‐PDGFR. Expression of cyclin D1, PDGFR, Notch1, and Hes1 was markedly enhanced by PDGF‐BB but inhibited by DAPT. In vitro angiogenesis assay showed that hEPCs/hMSCs coculture and PDGF‐BB significantly enhanced angiogenic capacity, whereas AB‐PDGFR significantly reduced the angiogenic capacity. PDGF‐BB increased the expression of kinase insert domain receptor (KDR, an endothelial marker) and activated Notch1 signaling in cocultured cells, while DAPT attenuated the promoting effect of PDGF‐BB on KDR expression of hEPCs/hMSCs coculture. hEPCs/hMSCs coculture enhanced their proliferation and angiogenic capacities. PDGF and Notch signaling pathways participated in the promoting effects of hEPCs/hMSCs coculture, and there was crosstalk between these two signaling pathways. Our findings should aid understanding of the mechanism of beneficial effects of hEPCs/hMSCs coculture. Abstract : This study aimed to investigate the effects of direct contact coculture of human endothelial progenitor cells (hEPCs) and human mesenchymal stem cells (hMSCs) on their proliferation and angiogenic capacities and the underlying mechanism. The proliferation and angiogenic capacities of both cell types were enhanced by their coculture. PDGF and Notch signaling pathways participated in the promoting effects of hEPCs/hMSCs coculture.